Feline Morbillivirus, a New Paramyxovirus Possibly Associated with Feline Kidney Disease - Eun Jin Choi (Viruses, 2020)
Feline morbillivirus (FeMV) was first isolated in stray cats in Hong Kong in 2012. Since its discovery, the virus has been reported in domestic cats worldwide, including in Hong Kong, Japan, Italy, US, Brazil, Turkey, UK, Germany, and Malaysia. FeMV is classified in the Morbillivirus genus within the Paramyxoviridae family. FeMV research has focused primarily on determining the host range, symptoms, and characteristics of persistent infections in vitro. Importantly, there is a potential association between FeMV infection and feline kidney diseases, such as tubulointerstitial nephritis (TIN) and chronic kidney diseases (CKD), which are known to significantly affect feline health and survival. However, the tropism and viral entry mechanism(s) of FeMV remain unknown. In this review, we summarize the FeMV studies up to date, including the discoveries of various FeMV strains, basic virology, pathogenicity, and disease signs.